Optimal Tibial Tunnel Placement for Medial and Lateral Meniscus Root Repair on the Anteromedial Tibia in the Setting of Anterior and Posterior Cruciate Ligament Reconstruction of the Knee. Issue 5 (April 2022) - Gursoy, Safa; Perry, Allison K.; Brady, Alex; Dandu, Navya; Singh, Harsh; Vadhera, Amar S.; Yanke, Adam B.; LaPrade, Robert F.; Chahla, Jorge
Background: Although the risk of tibial tunnel convergence in the setting of multiligamentous reconstruction has been reported in the literature, the risk of tunnel convergence in the setting of posterior cruciate ligament (PCL), anterior cruciate ligament (ACL) reconstruction and medial and lateral meniscus root repair has not been defined. Purpose: To examine the risk of tunnel convergence and to determine optimal tunnel placement for ACL and PCL reconstruction performed in conjunction with posterior medial and lateral meniscus root repairs on the anteromedial proximal tibia. Study Design: Descriptive laboratory study. Methods: Three-dimensional (3D) tibial models were created using computed tomography scans of 20 cadaveric specimens. After determining optimal tunnel entry and exit points for ACL and PCL reconstructions, and medial and lateral meniscus root reattachment to the anatomic footprints, we used image processing software to create root tunnels over the anteromedial tibia on the tibial models. ACL and PCL tunnels were kept constant. The meniscus root repair tunnels were then reoriented to match the angle of the ACL tunnel, making both tunnels parallel in the sagittal plane. Tunnel convergence risk was analyzed by identifying the shortest 3D distance between tunnel axes and subtracting the radius of each tunnel from this distance for single- and double-tunnel repair techniques in both case scenarios. Results: All specimens demonstrated convergence between the ACL and lateral meniscus root tunnels when the root tunnel's entry was created proximal to the ACL tunnel's entry for single- and double-tunnel techniques, but no convergence was seen between these tunnels using the parallel orientation in the sagittal plane. There were no cases of convergence between the ACL and medial meniscus root tunnels in any of the configurations. The greatest distance between the ACL and medial meniscus root tunnels was achieved using the single-tunnel technique in parallel orientation (12.1 ± 2.8 mm). There were no cases of convergence between the PCL and medial meniscus root tunnels in the original orientation; however, 2 of 20 specimens demonstrated convergence using the parallel orientation with the double-tunnel technique, and there were no cases of convergence using the single-tunnel technique. The PCL and lateral meniscus root tunnels did not demonstrate convergence in any configuration. Conclusion: There was a high risk of convergence between ACL and posterior meniscus root tunnels when all the tunnels were created on the anteromedial tibia. Reorienting meniscus root tunnels parallel to ACL tunnels may help reduce this risk. There is increased risk of tunnel convergence with root repairs in cases of bicruciate reconstructions, and therefore a double-tunnel root repair technique should be used with caution. Clinical Relevance: To avoid tibial tunnel convergence when performing ACL and PCL reconstruction with medial and lateral meniscus root repair, surgeons should reorient the meniscus root repair tunnels to be parallel on the sagittal plane to the ACL tunnel to decrease the risk of convergence. In cases of bicruciate ligament reconstruction, use of the double-tunnel technique requires caution to avoid convergence risk with the PCL tunnel.